Prone Positioning and Intravenous Zanamivir may Represent Effective Alternatives for Patients with Severe ARDS Virus A (H1N1) Related Pneumonia in Hospitals with no Access to ECMO. (11th July 2010) - Gristina, Giuseppe; Nardi, Giuseppe; Orazi, Daniela; Lauria, Francesco Nicola; Valli, Maria Beatrice; Lalle, Eleonora; Menzo, Stefano; Riccioni, Luigi; Camporiondo, Maria Pia
Abstract : The first patient with influenza A/H1N1-related pneumonia was admitted to an Italian ICU at the end of August 2009. Until then, despite the international alarm, the level of awareness was low and very few Italian hospitals were equipped with ECMOs. Moreover the PCR test for A H1N1 virus was sporadically available and the emergency departments of even the largest institutions could rely only on the rapid test for the urgent screening of patients with pneumonia and respiratory failure. On September 5th, a young and "apparently" previously healthy man, was admitted to our ICU because of a severe ARDS caused by influenza A H1N1 virus. As there was no ECMO available, he was treated with prolonged cycles of prone positioning ventilation. Antiviral treatment was started with Oseltamivir, but as enteral absorption was impaired by paralytic ileus and tube feeding intolerance, Oseltamivir had to be discontinued. Intravenous Zanamivir 1200 mg/day for ten days was therefore prescribed as "off label" antiviral therapy. A bone marrow biopsy allowed the diagnosis of an initial stage of "hairy cells leukaemia." ARDS related to A/H1N1 influenza was the first sign of the disease in our patient. He did well with complete clearance of the infection from the BAL after 10 days of Zanamivir, although the nasopharyngeal swabs remained positive for ten more days. Prone positioning ventilation may be a life-saver strategy in patients with severe ARDS when ECMO is not immediately available. However, prone positioning ventilation is often associated with severe impairment of the absorption of drugs that require enteral administration via the nasogastric tube. In these cases, intravenous Zanamivir may be an effective alternative strategy.